2022
DOI: 10.3390/axioms11120689
|View full text |Cite
|
Sign up to set email alerts
|

Confidence Intervals for the Ratio of Variances of Delta-Gamma Distributions with Applications

Abstract: Since rainfall data often contain zero observations, the ratio of the variances of delta-gamma distributions can be used to compare the rainfall dispersion between two rainfall datasets. To this end, we constructed the confidence interval for the ratio of the variances of two delta-gamma distributions by using the fiducial quantity method, Bayesian credible intervals based on the Jeffreys, uniform, or normal-gamma-beta priors, and highest posterior density (HPD) intervals based on the Jeffreys, uniform, or nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Like Threshold1, Threshold2 can be determined using a confidence interval approach, ensuring that it captures the variability in texture features observed within crack areas with a certain level of confidence [24,25].…”
Section: Mathematical Analysis For Variance Thresholdmentioning
confidence: 99%
“…Like Threshold1, Threshold2 can be determined using a confidence interval approach, ensuring that it captures the variability in texture features observed within crack areas with a certain level of confidence [24,25].…”
Section: Mathematical Analysis For Variance Thresholdmentioning
confidence: 99%
“…Several researchers have investigated rainfall dispersion in Thailand, such as Kumphon et al [3], Szyniszewska and Waylen [4], and Thodsan et al [5]. Additionally, studies on statistical inference for rainfall distribution in Thailand have been reported by Maneerat et al [6], Khooriphan et al [7], Yosboonruang et al [8,9], and Thangjai et al [10]. Previous research on statistical inference has primarily focused on measuring rainfall dispersion using variance and coefficient of variation.…”
Section: Introductionmentioning
confidence: 99%